Dysprosium doped novel apatite-type white-emitting phosphor Ca9La(PO4)5(GeO4)F2 with satisfactory thermal properties for n-UV w-LEDs. (April 2017) - Zhang, Yuanyuan; Mei, Lefu; Liu, Haikun; Yang, Dan; Liao, Libing; Huang, Zhaohui
Abstract: A novel apatite structure phosphor Ca9 La(PO4 )5 (GeO4 )F2 :Dy 3+ (CLPGF:Dy 3+ ) with a hexagonal lattice in the P 63 / m space group was synthesized via a facile solid state technique. The crystal and fine local structure as well as their photoluminescence properties were investigated in detail. The CLPGF:Dy 3+ phosphor can absorb in the UV-vis spectral region of 290–475 nm and exhibit two intense emission bands centered at 485 and 580 nm, which ascribes to 4 F9/2 → 6 H15/2 and 4 F9/2 → 6 H13/2 transitions of Dy 3+, respectively. The concentration quenching of Dy 3+ emission occurs via the energy transfer among the nearest-neighbor ions and the corresponding quenching mechanism was verified to be the dipole-dipole interaction. The quantum efficiencies of the phosphors were examined to be 72.9% and its luminescence intensity at 150 °C decreases to 93.8% and 98.6% of the initial value at room temperature, which corresponds to 4 F9/2 to 6 H15/2 transition and 4 F9/2 to 6 H13/2 transition of Dy 3+ ions, respectively. Their interesting photoluminescence properties indicate that the CLPGF:Dy 3+ phosphor is a promising white-emitting candidate for w -LEDs applications. Highlights: A novel apatite-type Ca9 La(PO4 )5 (GeO4 )F2 :Dy 3+ phosphor has been synthesized. Ca9 La(PO4 )5 (GeO4 )F2 :Dy 3+ is a promising white-emitting phosphor for LED. The Ca9 La(PO4 )5 (GeO4 )F2 :Dy 3+ phosphor shows excellent thermal stability.